The Absence of an Ocean and the Fate of Water all Over the Martian History - Giovanni Leone (Earth and Space Science, 2020)
Abstract Existing data returned in >40 years of planetary missions to Mars provided a good basis to understand that an ocean never existed on the surface of the planet during its whole history. The presence of environmental indicators like unaltered jarosite and olivine deposited by the early volcanic activity can be seen as evidence that liquid water was never abundant nor widespread on the surface of Mars since the pre‐Noachian or Noachian at least. There is a dramatic mismatch with the water equivalent volume of the outflow channels sources with the volume needed to form an ocean. The ubiquitous presence of large volcanoes, with their huge lava fields exactly where liquid water was claimed to be abundant during the Noachian age, makes now very clear that lava and not water was involved in the formation of the outflow channels and the fluvial networks. As a consequence, cheaper robotic exploration might be favored with respect to the ambitious human exploration program planned for Mars. Unless enough water supplies will be brought to the equatorial regions from the poles through long pipelines, or from nearby asteroids through cargo ships, it will be very difficult to exploit the rich equatorial resources brought up from the mantle by the massive volcanism that characterized the early history of the planet. Digging deeply the equatorial regions searching for water would be too expensive, of uncertain reward, and thus unpractical.